2019
DOI: 10.1038/s41433-019-0397-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term natural history of idiopathic epiretinal membranes with good visual acuity

Abstract: Background/objectives To evaluate the long-term progression of idiopathic epiretinal membranes (iERMs) with good baseline visual acuity, and to identify predictors of visual decline. Design Retrospective case series Subjects methods We reviewed records of 145 eyes with iERM and best-corrected visual acuity (BCVA) of 20/40 or greater at presentation, including BCVA, lens status, and central macular thickness (CMT) at yearly visits; as well as anatomic biomarkers including vitreomacular adhesion, pseudohole, lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The results of this study are in agreement with another long-term follow-up of patients with ERMs by Luu et al [8] with a minimum of 1-year follow-up and a shorter mean follow-up than our study (3.7 years). In that study, patients experienced a slow decline of visual acuity (0.012 ± 0.003 LogMAR per year) with 21% of the patients undergoing vitrectomy and membrane peeling [8]. The incidence of patients demonstrating ellipsoid zone loss was also similar to our study, as 41% of patients developed ellipsoid zone loss, compared with 37% in our study [8].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study are in agreement with another long-term follow-up of patients with ERMs by Luu et al [8] with a minimum of 1-year follow-up and a shorter mean follow-up than our study (3.7 years). In that study, patients experienced a slow decline of visual acuity (0.012 ± 0.003 LogMAR per year) with 21% of the patients undergoing vitrectomy and membrane peeling [8]. The incidence of patients demonstrating ellipsoid zone loss was also similar to our study, as 41% of patients developed ellipsoid zone loss, compared with 37% in our study [8].…”
Section: Discussionsupporting
confidence: 93%
“…Pars plana vitrectomy and ERM peeling, first described by Machemer in 1978 [6], has become the established surgical treatment for visually significant ERM [4, 7]. However, ERMs may be safely observed if the visual acuity is good or the patient has minimal symptoms [8].…”
Section: Introductionmentioning
confidence: 99%
“…33,34 The size of the largest intraretinal cyst for each eye was also measured based on the horizontal diameter as described in previous studies of OCT biomarkers. 35,36 Eyes with SRF were quantified for SRF thickness based on the linear distance perpendicular to the RPE. SRF thickness was considered ungradable if signal attenuation, or "shadowing," from overlying intraretinal fluid prevented accurate measurement of SRF thickness.…”
Section: Image Gradingmentioning
confidence: 99%
“…Patients symptoms range from being completely asymptomatic to complaining of metamorphopsia and loss of vision depending on macular involvement [ 4 ]. Disease progression leads to gradual but mild vision loss, a retrospective study reported that 21% of patients required surgery at 4 years if baseline visual acuity was ≥ 20/40 [ 8 ]. Treatment options consist of mainly in watchful waiting or vitrectomy surgery with peeling of the membrane [ 9 ].…”
Section: Introductionmentioning
confidence: 99%